1999
DOI: 10.1038/22146
|View full text |Cite
|
Sign up to set email alerts
|

Single kinesin molecules studied with a molecular force clamp

Abstract: Kinesin is a two-headed, ATP-driven motor protein that moves processively along microtubules in discrete steps of 8 nm, probably by advancing each of its heads alternately in sequence. Molecular details of how the chemical energy stored in ATP is coupled to mechanical displacement remain obscure. To shed light on this question, a force clamp was constructed, based on a feedback-driven optical trap capable of maintaining constant loads on single kinesin motors. The instrument provides unprecedented resolution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

86
1,099
8
5

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 953 publications
(1,205 citation statements)
references
References 31 publications
86
1,099
8
5
Order By: Relevance
“…(29) ATP hydrolyzed. (33,34) Thermal fluctuations are expected to play an important role in the motor mechanism, either by driving diffusional movements of the motor to its next binding position (35) or by promoting diffusive structural changes that drive force-producing conformational changes. (30) The structural elements that undergo strain have not been identified with certainty for any molecular motor, but are likely to have spring-like or elastic properties that allow them to extend or rotate, then recoil back into their original conformation.…”
Section: Introductionmentioning
confidence: 99%
“…(29) ATP hydrolyzed. (33,34) Thermal fluctuations are expected to play an important role in the motor mechanism, either by driving diffusional movements of the motor to its next binding position (35) or by promoting diffusive structural changes that drive force-producing conformational changes. (30) The structural elements that undergo strain have not been identified with certainty for any molecular motor, but are likely to have spring-like or elastic properties that allow them to extend or rotate, then recoil back into their original conformation.…”
Section: Introductionmentioning
confidence: 99%
“…A more specialized version of the model further proposes that run lengths are determined by random detachment of engaged motors, promoted by this load. As mentioned above, in vitro molecular motor studies have shown that motor velocity depends on load [19][20][21] such that motors move faster when under less load. Further, there is evidence that when multiple motors work together under negligible opposing load, the catalytic rate of each individual motor is not altered [26].…”
Section: Force-velocity Relationship In Vivo: Survey Of Existing Resultsmentioning
confidence: 94%
“…biochemical regulation, are of secondary importance. This proposal stems from in vitro observations [19][20][21] showing that load on a motor decreases its processivity and velocity. Thus, if motors share the load opposing cargo motion, then removal of a motor from the engaged motor pool will increase load on a per-motor basis, and thus decrease cargo velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Single molecule imaging methods have been pivotal in the experimental study of molecular motor dynamics 8,9 . Such advanced techniques have allowed researchers to dissect various aspects of molecular motor mediated transport 10,11,12,13,14,15 .…”
Section: Introductionmentioning
confidence: 99%